Multispecies environmental DNA metabarcoding sheds light on annual coral spawning events - Ip, Yin Cheong Aden; Chang, Jia Jin Marc; Tun, Karenne Phyu Phyu; Meier, Rudolf; Huang, Danwei (Molecular ecology, 2023)
Synchronous multispecific coral spawning generally occurs annually and forms an integral part of the coral life cycle. Apart from spawning times and species participation, however, much else remains unknown. Here, we applied environmental DNA (eDNA) metabarcoding to study two tropical reef sites of contrasting coral cover before, during and after coral spawning. Using coral‐ITS2 and vertebrate‐12S markers, we evaluated eDNA as an alternative monitoring tool by assessing its capabilities in detecting spawning species and tracking relative abundances of coral and fish eDNA. Over 3 years, elevated eDNA coral signals during the event (proportional read increase of up to five‐fold) were observed, detecting a total of 38 coral and 133 fish species with all but one of the coral species visually observed to be spawning. This is also the first demonstration that eDNA metabarcoding can be used to infer the diurnal partitioning of night‐ and day‐time spawning, spawning in coral species overlooked by visual surveys, and the associated changes in fish trophic structures as an indicator of spawning events. Our study paves the way for applied quantitative eDNA metabarcoding approaches to better study ephemeral and important biological events.